Biofidelic conductive soft tissue surrogates. Issue 2 (22nd January 2020) - Chanda, Arnab; Unnikrishnan, Vinu; Lackey, Kim; Robbins, Joseph
Abstract: Surrogates which can simulate the biomechanical behavior of soft tissues and exhibit electrical properties, are critical for development of biomedical devices and wearable technologies, for collection of physiological information related to performance and clinical diagnosis. Based on recent advances in fabrication of biofidelic soft tissues from various locations on the human body, the current work aimed to develop an experimental framework for fabricating conductive surrogates, which can mimic the non-linear mechanical behavior, and modulus of elasticity at high and low strains of soft tissues. The material model utilizes short carbon fibers embedded within a four-part elastomeric matrix material. Multiple test coupons were generated with different fiber lengths and fiber weight fractions (FWFs), and their mechanical properties and electrical conductivities were characterized. The electrical changes due to stretching were quantified and microscopy was used to observe the changes in fiber distribution due to varying FWF and strains. Surrogate compositions with optimal fiber lengths and FWFs were identified to simulate mechanical properties of the human skin, muscles, pelvic tissues, brain tissues and arteries. Graphical Abstract: